Impact of third molars on mandibular relapse in post-orthodontic patients: A meta-analysis - Hsin-Chung Cheng; Bou-Yue Peng; Hsueh-Yin Hsieh; Ka-Wai Tam (Elsevier, 2018)
Background/purpose: Whether third molars contribute to or aggravate relapse, particularly in the mandibular dental arch, after orthodontic treatment remains controversial. Orthodontic clinicians vary widely in their practice regarding prophylactic third molar removal after orthodontic treatment. The present study systematically reviewed and meta-analyzed the available literature, and assessed the impact of third molar removal on the relapse of mandibular dental arch alignment after orthodontic treatment. Materials and methods: Relevant literature was searched on online databases, namely Pubmed, Embase, and Cochrane. Outcomes of post-orthodontic mandibular relapse were evaluated in terms of the Little's irregularity index, intermolar width, and arch length. Statistical analysis was conducted using the Review Manager software (Version 5.3, The Cochrane Collaboration, Oxford, England). Results: Our initial search strategy yielded 360 citations, of which three retrospective studies were selected. The Little's irregularity index (weighted mean difference = 0.80, 95% confidence interval = 0.13-1.47, P = 0.02) differed significantly between the erupted third molar extraction group and agenesis third molar group; whereas the arch length and intermolar width did not. No outcome differed significantly between the impacted third molar extraction group and agenesis third molar group. Conclusion: Removal of the mandibular third molars is recommended for alleviating or preventing long-term incisor irregularity. Keywords: little's irregularity index, post-orthodontic mandibular relapse, prophylactic third molar removal, third molars